Pancasila Adventure: An Android-Based Educational Game Innovation to Sharpen Vocational Students' Critical Thinking Skills - Rini , Ajeng Setyo; Atok , A. Rosyid Al (Universitas Muhammadiyah Makassar, 2026)
The urgency of this research arises from the limited availability of engaging and interactive learning media in Pancasila education, particularly at the vocational high school level. The dominance of one-way learning methods results in low student participation and limited opportunities to develop higher-order thinking skills (HOTS). This research aims to develop an educational game, Pancasila Adventure, that is valid, practical, engaging, and effective, oriented towards improving students' critical thinking skills. This research adopts the Lee and Owens (2004) development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The validation results from material experts obtained a score of 96.7, and from media experts 88.5—both categorized as very valid. The practicality test achieved a score of 4.7 (practical), while the small and large group trials scored 83 and 84 (engaging), respectively. The effectiveness test showed an average score of 83 (effective). This research integrates the improvement of critical thinking with HOTS-based interactive games, providing both theoretical and practical contributions to the development of game-based learning in Pancasila education.